2009
DOI: 10.2147/ccide.s6760
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of photography in maxillofacial surgery: from analog to 3D photography – an overview

Abstract: In maxillofacial surgery, digital photographic documentation plays a crucial role in clinical routine. This paper gives an overview of the evolution from analog to digital in photography and highlights the integration of digital photography into daily medical routine. The digital workflow is described and we show that image quality is improved by systematic use of photographic equipment and post-processing of digital photographs. One of the advantages of digital photography is the possibility of immediate reap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…While direct anthropometry has always been accepted as the gold standard in facial analysis because of its simplicity and low cost, the need for long clinical sessions and well-trained examiners has been a hindrance [30][31][32] . Stereophotogrammetry presents a safe, non-invasive technique free of ionizing radiation in longitudinal studies 33 . Several papers present promising results for the use of this technique, but inconsistent terminologies and statistical tests for error analysis are a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…While direct anthropometry has always been accepted as the gold standard in facial analysis because of its simplicity and low cost, the need for long clinical sessions and well-trained examiners has been a hindrance [30][31][32] . Stereophotogrammetry presents a safe, non-invasive technique free of ionizing radiation in longitudinal studies 33 . Several papers present promising results for the use of this technique, but inconsistent terminologies and statistical tests for error analysis are a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…These technological advancements have unleashed medical professionals’ ability to document a patient’s clinical progression, including details for wound documentation, for example, to avoid repeated medical examinations, and seeing wound progression over time [ 5 , 6 ]. In medical fields that rely heavily on visual physical examinations, such as plastic surgery [ 7 ], maxillo-facial surgery [ 8 ], and orthopaedic surgery [ 9 ], medical photography can also significantly help patient care [ 10 , 11 ]. Among dermatologists that frequently inspect suspicious lesions, one study found that 89% of the respondents agree that medical photography facilitates patient care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It used a CCD (Charge-coupled-device) sensor, which consists of a panel of photosensitive diodes that capture the image data together with a storage panel that picks up the images and represents an analog-moving register. This allows the analogic signals (electric charge) to be transported in several successive steps under the control of a clock signal [ 7 ].…”
Section: Introductionmentioning
confidence: 99%